Use of lightweight materials in 21st century army trucks (National Academies Press, 2003)
Provides information on how, in order to achieve the Army's envisioned Objective Force, the Committee on Lightweight Materials for the 21st Century Army Trucks was asked to identify research and technology development opportunities related to the introduction of lightweight structural materials for light medium and heavy Army trucks.